New Regions With Molecular Alterations in a Rare Case of Insulinomatosis: Case Report With Literature Review - Anoshkin, Kirill; Vasilyev, Ivan; Karandasheva, Kristina; Shugay, Mikhail; Kudryavtseva, Valeriya; Egorov, Alexey; Gurevich, Larisa; Mironova, Anna; Serikov, Alexey; Kutsev, Sergei; Strelnikov, Vladimir (Frontiers in Endocrinology, 2021)
Insulinomatosis is characterized by monohormonality of multiple macro-tumors and micro-tumors that arise synchronously and metachronously in all regions of the pancreas, and often recurring hypoglycemia. One of the main characteristics of insulinomatosis is the presence of insulin-expressing monohormonal endocrine cell clusters that are exclusively composed of proliferating insulin-positive cells, are less than 1 mm in size, and show solid islet-like structure. It is presumed that insulinomatosis affects the entire population of β-cells. With regards to molecular genetics, this phenomenon is not related to mutation in MEN1 gene and is more similar to sporadic benign insulinomas, however, at the moment molecular genetics of this disease remains poorly investigated. NGS sequencing was performed with a panel of 409 cancer-related genes. Results of sequencing were analyzed by bioinformatic algorithms for detecting point mutations and copy number variations. DNA copy number variations were detected that harbor a large number of genes in insulinoma and fewer genes in micro-tumors. qPCR was used to confirm copy number variations at ATRX, FOXL2, IRS2 and CEBPA genes. Copy number alterations involving FOXL2, IRS2, CEBPA and ATRX genes were observed in insulinoma as well as in micro-tumors samples, suggesting that alterations of these genes may promote malignization in the β-cells population.